Exploring post-rehabilitation plasticity with intra-cerebral recordings on anomic profiles - Trébuchon, Agnès; Fasola, Alexia; Sabadell, Véronique; Dubarry, Anne-Sophie; Carron, Romain; Bartolomei, Fabrice; Alario, F.-Xavier (Frontiers in Language Sciences, 2025)
Background: Patients with drug-resistant epilepsy involving the language network often exhibit anomic profiles in daily life due to difficulties with lexical selection processes. There is very little evidence available regarding the effects of language rehabilitation in this population.We aim to induce brain plasticity combined with improvements in behavioral performance through language therapy in patients with epilepsy.We implemented a therapy focused on phonological and semantic features of infrequent words over three treatment sessions, each targeting a specific semantic category. Intracranial signals were recorded in 10 patients during baseline and post-therapy picturenaming sessions. Response time and percentage of correct responses during naming tests were collected. Time-frequency analyses were conducted on intracranial signals, and comparisons were made between baseline and post-therapy conditions for each patient.Results: Half of the patients demonstrated improved naming skills following the treatment. We observed significantly different recruitment of frontotemporal areas in the left hemisphere (including "Broca's Area") post-therapy in patients that improved naming skills. Specifically, we found significantly different high-gamma activity in the posterior left inferior frontal gyrus 500 ms after stimulus onset in patients with improved naming skills vs non-improved naming skills. This effect was not observed in the right hemisphere.Conclusions: These findings suggest that enhanced performance following language therapy is associated with modifications in posterior left IFG activations during latencies closely tied to the lexical selection process.